PENGARUH RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP RETURN SAHAM PADA PT CATUR SENTOSA ADIPRANA TBK PERIODE TAHUN 2013-2022 - Daraga, Iqbal; Yusran Daeng Matta (Journal of Research and Publication Innovation, 2024)
This research aims to find out the impact of Return on Asset (ROA) and Return On Equity (ROE) on the Return of Shares in PT. Chatur Sentosa Adiprana Tbk. Period 2013-2022 both a partial ceremony and simultaneously. The independent variables used in the study are Return on Asset (ROA) and Return On Equity (ROE) while the dependent variables that are used in this study are Stock Return. The research method used in this research is quantitative. The type of data used in this research is secondary data. Population in this study is the financial report of PT. Chatur Sentosa Adiprana Tbk. Period 2013-2022. The sample used in the research is the balance sheet report, loss and share price summary of PT Chatur Sentosa Adiprana Tbk. Data analysis techniques used are descriptive analysis tests, classical assumption tests, double linear regression tests, hypothesis tests and determination coefficient tests with SPSS 26 application. The initial results showed that partially Return On Asset has no significant influence on the return of shares where 1.045 < ttable 1.89458 with a significance value of 0.331 > 0.05. partially the return on equity has no major influence over return of stocks where -0.249 < t table 1.89 458 with the significance of 0.811 > 05. Simultaneously, Return on Asset and ReturnOn Equity have a significant impact on return of stock where the value of Fcalung 7.644 > Ftable 4.737 with a signification value of 0.01 < 0.05. To improve the return on assets and return on equity through a strategy to increase profits, improve operational efficiency, make strategic investments.